Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/odi.13073
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin‐3‐gallate inhibits proliferation and induces apoptosis in odontogenic keratocyst keratinocytes

Abstract: Objective The aim of this study was to investigate the effects of epigallocatechin‐3‐gallate on the proliferation and apoptosis of odontogenic keratocyst (OKC) keratinocytes in vitro. Materials and methods Keratinocytes isolated from the epithelial lining of the OKC were cultured in keratinocyte serum‐free medium and identified by CK10, CK14, pan‐cytokeratin and vimentin immunofluorescence staining. The cells were exposed to EGCG at different concentrations, and proliferation inhibition was measured by cell co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Catechin is a substance abundant in green tea and many studies approved its anticancer effects (Buttet al, 2015;Ohishi et al, 2016). These effects can be due to its role in apoptotic and signaling pathways (Kumar et al, 2019;Yang et al, 2019). The cytotoxic and apoptotic effects of S. rhombifolia extract may be attributed to the presence of epicatechin, why so it has also been present in S. rhombifolia to a great extent than other compounds and its apoptotic effects have been confirmed in other studies.…”
Section: Discussionmentioning
confidence: 86%
“…Catechin is a substance abundant in green tea and many studies approved its anticancer effects (Buttet al, 2015;Ohishi et al, 2016). These effects can be due to its role in apoptotic and signaling pathways (Kumar et al, 2019;Yang et al, 2019). The cytotoxic and apoptotic effects of S. rhombifolia extract may be attributed to the presence of epicatechin, why so it has also been present in S. rhombifolia to a great extent than other compounds and its apoptotic effects have been confirmed in other studies.…”
Section: Discussionmentioning
confidence: 86%
“…C-Jun N-terminal kinase (JNK) signaling makes a critical difference in controlling tissue polarity, and the potential therapeutic effect of EGCG on odontogenic keratocysts through modulation of the wingless/integrated (WNT)/ JNK signaling pathway has been demonstrated. 32,33 In the tongue, EGCG might act similarly on the WNT/JNK pathway to improve cell polarity.…”
Section: Egcg Relieves Tongue Inflammationmentioning
confidence: 99%
“…Cerezo-Guisado et al (2015) found that EGCG induces cell death in colon cancer cell line (HT-29 cells) and it has cytotoxic effects and has a cancer preventive role. Yang et al (2019) stated that EGCG induces apoptosis by inhibiting proliferation in odontogenic keratocyst keratinocytes by suppressing the WNT/JNK signaling pathway. Jankun et al (2014) stated that EGCG had better efficacy to prevent tumor cell growth than mitomycin C (MMC) when they compared EGCG and MMC in rats with superficial bladder cancer.…”
Section: Anticancer and Antitumor Effect Of Epigallocatechin-3 Gallatementioning
confidence: 99%